Is South Africa ready for point-of-care, non-sputum tests for TB diagnosis? An assessment of end-user perceptions on a novel urine test and tongue swab for TB testing - Nasiphi Mqedlana-Ntombela; Vanessa Fargnoli; Salome Charalambous; Kavindhran Velen; Sonjelle Shilton; Violet Chihota (BMC Health Services Research)
Abstract Background Sputum collection continues to limit TB testing, resulting in undiagnosed TB. Innovative interventions are needed to expand point-of-care TB diagnosis particularly in low-to-middle income countries (LMICs). Novel non-sputum sample types currently under development can increase TB testing, however there is limited knowledge on end-user perceptions on these tests. Methods Between March and June 2023, we conducted a mixed methods study to assess end-user insights on a tongue swab and urine test currently under development for TB diagnosis. To describe the sample types to respondents, we used visual information sheets. Surveys were conducted among TB care recipients, healthcare workers, public health experts and civil society stakeholders, while semi-structured interviews were with all groups except for TB care recipients. The surveys were analysed descriptively, and thematic analysis was used for the semi-structured interviews. Results The median acceptability for the urine test and tongue swab were 94.85% and 96.8% respectively. While the acceptability of the novel tests was high, respondents identified potential barriers that would negatively impact effective implementation and utility if not addressed. The identified barriers included patient level factors such as collection of midstream urine for the urine test, clinic and healthcare provider factors such as the time required to process test results, and contextual factors such as power and water outages, as well as stock shortages common in South African health facilities. Conclusions Both novel sample types were highly acceptable and preferred over sputum collection. There are however potential barriers identified by end-users that need that would affect effective implementation and utility if not addressed. Manufacturers need to consider patient, provider, gender, and context specific factors during the development of novel innovations for effective uptake and implementation.